"Everything is technology": Examining technology access and use among returning citizens - Sanders, Kaelyn (Criminology & public policy, 2025)
Research summary Digital inequality is a barrier for returning citizens. Yet, much remains unknown about the specific issues they encounter. As the world continues to advance technologically, it is important that we understand returning citizens’ access to and use of technology and how it impacts their ability to reintegrate into society. Framed in the Digital Rehabilitation Model, the current study uses qualitative data from 28 returning citizens to explore their experiences with digital exclusion. Findings show that returning citizens have challenges accessing and using technology in several reentry areas. Policy implications The study's results reflect returning citizens’ need for support to access and use technology for reentry purposes. Specifically, they need assistance with accessing computers and using technology for online job searching, education, and other personal needs. In addition, they also need education on how to maintain online safety. Policy recommendations are given for how correctional facilities can work with existing organizations and frameworks to increase returning citizens’ access to technology, the Internet, and digital skills programming prior to and after release from prison. In addition, concerns about how to maintain prison safety and security while increasing access to technology devices and the Internet are addressed.